Estimates of Classes of Generalized Special Functions and Their Application in the Fractional k, s-Calculus Theory. (6th October 2021) - Chandak, S.; Suthar, D. L.; AL-Omari, S.; Gulyaz-Ozyurt, S.
Abstract : In this article, we aim to develop new k, s -fractional integral and differential operators containing S -functions as kernels in a form of generalized k -Mittag-Leffer functions. We also set up various properties of such operators. Furthermore, we consider a variety of implications of the major outcomes that will be very useful in the implementation of scientific, engineering, and technical problems.